2006
DOI: 10.1063/1.2339024
|View full text |Cite
|
Sign up to set email alerts
|

Electron energy distribution functions in low-pressure inductively coupled bounded plasmas

Abstract: The electron energy distribution function ͑EEDF͒ in a low-pressure inductively coupled plasma confined between two infinite plates separated by 10 cm is investigated using a one-dimensional particle-in-cell simulation including Monte Carlo collisions. At low pressure, where the electron mean free path is of the order of or greater than the system length, the EEDF is close to Maxwellian, except for its tail, depleted at high energy. We give clear evidence that this depletion is mostly due to the high-energy ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
56
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 36 publications
(30 reference statements)
4
56
1
Order By: Relevance
“…10 The resulting upstream EEPF reveals a depleted tail corresponding to the downstream EEPF indicating energetic electrons upstream of the DL possess sufficient energy to overcome the potential drop of the DL and neutralize the beam of ions accelerated by the DL, in good agreement with one-dimensional particlein-cell simulations ͑with three-dimensional treatment of collisions͒. 15 Subsequent radial measurements of the EEPF upstream of the DL have demonstrated a significant distinction between the central and peripheral EEPFs. 21 In the present study, a region of bi-Maxwellian EEPF, accompanying an increase in the measured ion and electron density, is identified which separates two regions of Maxwellian EEPFs: a cold electron population near the chamber walls and a hotter Maxwellian population in the central region where the ion beam is detected.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…10 The resulting upstream EEPF reveals a depleted tail corresponding to the downstream EEPF indicating energetic electrons upstream of the DL possess sufficient energy to overcome the potential drop of the DL and neutralize the beam of ions accelerated by the DL, in good agreement with one-dimensional particlein-cell simulations ͑with three-dimensional treatment of collisions͒. 15 Subsequent radial measurements of the EEPF upstream of the DL have demonstrated a significant distinction between the central and peripheral EEPFs. 21 In the present study, a region of bi-Maxwellian EEPF, accompanying an increase in the measured ion and electron density, is identified which separates two regions of Maxwellian EEPFs: a cold electron population near the chamber walls and a hotter Maxwellian population in the central region where the ion beam is detected.…”
mentioning
confidence: 56%
“…Investigation into the formation of DLs and the related ionic and electronic behavior in one dimension have been performed experimentally, 1-10 analytically, [11][12][13] and through simulation. 5,14,15 Further development of the HDLT now requires investigation into the two-dimensional nature of the related physics, including the effects of magnetic fields and mechanical geometry. 8 Experiments have previously characterized the beam and bulk ions two dimensionally using retarding field energy analyzers ͑RFEAs͒ and Langmuir probes.…”
mentioning
confidence: 99%
“…In recent laboratory experiments, supersonic ion beams accelerated by the DLs have been detected in magnetically expanding rf plasmas using retarding field energy analyzers (RFEAs) [7,8] and laser induced fluorescence methods [9,10,11]. It is reported that this type of DLs is maintained by only the single plasma source, where the upstream energetic electrons overcoming the potential drop of the DL neutralize the ion beam accelerated by the DL [12,13,14]. The electrodeless ion acceleration mechanism is proposed to be utilized for development of a new type of electrodeless long-lifetime propulsion device [5,15].…”
Section: Introductionmentioning
confidence: 99%
“…The break energy tracks the value of φ p at the center of the plasma [9]. The EEPFs comprise of low energy trapped electrons whose energies are below the break energy (i.e., below φ p ) and high energy escaping electrons whose energies are above the break energy (i.e., above φ p ).…”
Section: Figure 4 | Eepf In X Direction At the Center For (A) Differementioning
confidence: 99%
“…Godyak et al [8] looked at EEPF of inductively coupled plasma (ICP) in Argon over a wide range of pressure and power combinations. Meige and Boswell [9] looked at EEPF in an ICP to investigate the origin of the break energy at the plasma space potential. Bhattacharjee et al [10] looked at the effect of excitation frequency.…”
Section: Introductionmentioning
confidence: 99%